Food Security and Risk Reduction in Banglades - Habiba, U (Springer, 2015)
This book draws examples from food security issues in Bangladesh. The book is structured around those issues and underlying causes of food security, the implications from different sectors, policy analysis, and the role and actions of various stakeholders from different sectors to ensure food security.